A study on occupational stress of police women employees in Kerala - Sivadas, Kalpa; Rajalakshmi, K. (Edelweiss Applied Science and Technology, 2024)
Occupational stress is very prevalent in challenging professions such as law enforcement, in particular among female police officers who face unique pressures stemming from both professional and gender-related demands. The objective of this study is to analyze the factors that lead to occupational stress among female police officers in Kerala and to establish an effective selection and support system to mitigate its impact. The study examines the influence of socio-economic, demographic, and job-related factors, such as age, marital status, education, designation, work experience, income, and frequency of transfers and training, on stress levels. Data for the study was gathered from 300 female police officers in various locations using customized questionnaires that utilized well-established methods for detecting stress. An empirical study was conducted to determine the primary stresses and analyze their relationship with demographic variables. According to research, female police officers who are younger, hold lower positions, those who undergo several relocations, and get fewer training opportunities tend to be more stressed out. Furthermore, the study unveiled that the disparity between professional and personal life, together with the socio-economic standing, exerted a significant impact on the degrees of stress encountered. Furthermore, the combination of work-life balance and socio-economic status significantly impacts stress levels. This study emphasizes the need of implementing a customized recruitment and training strategy that considers these factors, offering essential insights for police agencies to enhance their recruitment and support services. The present study utilized various methodological approaches to examine the correlation between stress and well-being. The findings demonstrate a significant negative correlation between work-related stress and well-being (r = -0.62, p < 0.001), accounting for 55% of the observed variation in job satisfaction that may be attributable to organizational stress. To enhance job performance and reduce turnover among female police officers, it is imperative to regularly carry out stress assessments and apply targeted interventions.